2022
DOI: 10.1007/s10995-022-03526-y
|View full text |Cite
|
Sign up to set email alerts
|

Shackling and pregnancy care policies in US prisons and jails

Abstract: y people to ensure healthy pregnancies. Yet, the right to give birth safely with dignity is not consistently protected for pregnant people behind bars (Hayes et al., 2020). Previous studies and lawsuits have documented the variable and inadequate care for pregnant people in custody (Peeler et ObjectivesNearly 4% of incarcerated women in the United States (US) are pregnant when incarcerated (Sufrin et al., 2019). Thus, carceral facilities are tasked with caring for pregnant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Of the sixteen included papers, six were from the United States of America (USA) (Ferszt & Clarke, 2012 ; Hackett, 2017 ; Kelsey et al, 2017 ; Kotlar et al, 2015 ; Kramer et al, 2023 ; Nair et al, 2021 ), four from the United Kingdom (UK) (Abbott, 2018 ; Abbott et al, 2023 ; Albertson et al, 2012 ; Bard et al, 2016 ), three from Iran (Alirezaei & Roudsari, 2020 , 2022a , 2022b ), two from Canada (Ifeonu et al, 2022 ; Kirubarajan et al, 2022 ), and one from Australia (Baldwin et al, 2020a ). Five of the included papers were literature reviews (Alirezaei & Roudsari, 2022a ; Baldwin et al, 2020a ; Bard et al, 2016 ; Kirubarajan et al, 2022 ; Nair et al, 2021 ), one a mixed methods study (Ferszt & Clarke, 2012 ), one a quantitative study (Kelsey et al, 2017 ), five qualitative studies (Abbott, 2018 ; Abbott et al, 2023 ; Alirezaei & Roudsari, 2022b ; Hackett, 2017 ; Ifeonu et al, 2022 ), two policy analyses (Alirezaei & Roudsari, 2020 ; Kramer et al, 2023 ), one a multi-component consultation paper (Albertson et al, 2012 ), and one a report (Kotlar et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the sixteen included papers, six were from the United States of America (USA) (Ferszt & Clarke, 2012 ; Hackett, 2017 ; Kelsey et al, 2017 ; Kotlar et al, 2015 ; Kramer et al, 2023 ; Nair et al, 2021 ), four from the United Kingdom (UK) (Abbott, 2018 ; Abbott et al, 2023 ; Albertson et al, 2012 ; Bard et al, 2016 ), three from Iran (Alirezaei & Roudsari, 2020 , 2022a , 2022b ), two from Canada (Ifeonu et al, 2022 ; Kirubarajan et al, 2022 ), and one from Australia (Baldwin et al, 2020a ). Five of the included papers were literature reviews (Alirezaei & Roudsari, 2022a ; Baldwin et al, 2020a ; Bard et al, 2016 ; Kirubarajan et al, 2022 ; Nair et al, 2021 ), one a mixed methods study (Ferszt & Clarke, 2012 ), one a quantitative study (Kelsey et al, 2017 ), five qualitative studies (Abbott, 2018 ; Abbott et al, 2023 ; Alirezaei & Roudsari, 2022b ; Hackett, 2017 ; Ifeonu et al, 2022 ), two policy analyses (Alirezaei & Roudsari, 2020 ; Kramer et al, 2023 ), one a multi-component consultation paper (Albertson et al, 2012 ), and one a report (Kotlar et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite one paper highlighting that 40% of prison officers do not believe that pregnant women should be treated any differently to the other inmates, inclusive of the food they were provided with (Kirubarajan et al, 2022 ), five studies reported that pregnant women were routinely provided with additional food or snacks (Alirezaei & Roudsari, 2020 ; Bard et al, 2016 ; Ferszt & Clarke, 2012 ; Hackett, 2017 ; Kramer et al, 2023 ), and others were given a ‘pregnancy pack’, bag or vouchers (Albertson et al, 2012 ; Hackett, 2017 ; Kelsey et al, 2017 ). The specific contents of the ‘pregnancy pack’ differs between institutions and are not normally itemised.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations